Post-storage Seed Quality in Cucumber (Cucumis sativus L.) as Impacted by Variable Fruit Age and in-situ Storage Durations - KARTIK PATHANIA; NAVJYOT KAUR; LAVANYA VIJ; SANJULA SHARMA; RAJINDER SINGH (Seed Research, 2025)
The contribution of fruit pulp reserves to seed development and post-harvest seed quality in cucurbitsremains inadequately explored, despite the widespread practice of in-situ fruit storage prior to seed extraction.The present investigation examined the combined influence of fruit harvest stage and in-situ storage duration ofharvested fruits on seed quality and longevity in cucumber (Cucumis sativus L.). Fruits were harvested at threedevelopmental stages, namely 30, 40 and 50 days after anthesis (DAA), and subjected to four in-situ storagedurations (0, 5, 10, and 15 days). Seeds extracted from each treatment were stored for eight months, duringwhich germination percentage and seedling vigour index-I were assessed at two-month intervals. Biochemicalconstituents, including total soluble sugars, starch, total soluble proteins, oil content, and total soluble aminoacids, were quantified immediately after seed extraction and after eight months of storage. Seed germinationpercentage and vigour index-I increased progressively with advancement in fruit maturity from 30 to 50 DAA andwith longer in-situ storage duration from 0 to 15 days. Seeds extracted from fruits harvested at 30 and 40 DAAexhibited an increase in germination up to four months of storage, whereas those harvested at 50 DAA showedimprovement up to six months, followed by a gradual decline. Storage reserves such as sugars, starch, proteins,and oil content declined with prolonged seed storage, accompanied by an increase in total soluble amino acids.Seeds harvested at 50 DAA and extracted after 10 days of in-situ fruit storage consistently exhibited superior seedquality and storability after eight months of storage. The study highlights the critical role of fruit maturity and postharvest fruit handling in optimizing seed quality and provides practical recommendations for improving cucumberseed longevity under typical storage conditions.